Auditor search periods as signals of engagement risk: Effects on auditor choice and audit pricing. (June 2017) - Mande, Vivek; Son, Myungsoo; Song, Hakjoon
Abstract: We examine the effect of auditor search periods (time taken from the dismissal/resignation of the old auditor to the appointment of the new auditor) on successor auditor choice and audit fees. Using a sample of auditor changes during the period 2002–2012, we find that clients associated with long search periods are less likely to be accepted by Big N auditors. Our results also show that successor auditors charge their clients higher initial audit fees following lengthier searches. Finally, we document that delays in appointing successor auditors following resignations are associated with a significantly negative stock market response. Our results suggest that investors, regulators and academics should be heedful of lengthy auditor search periods in their evaluations of audit quality and client risks.